Strategy to fulfill fiber requirement in children - Diana Sunardi (World Nutrition Journal, 2022)
Diet in childhood influences not only the immediate health of children but also may have an impact in a positive or negative manner on the future health status. Dietary fiber has many physiological effects including reducing postprandial glucose concentrations, improving fecal bulk, promoting laxation, interfering with fat and cholesterol absorption, and altering bacteria populations in the gut microbiome. The first years of life may be critical for the establishment of a healthy colonic microflora, as well as good eating habits.